Penguatan Self-Control Anak melalui Program Intervensi Berbasis Aktivitas di Panti Asuhan X - Putri D. Riyani; Ghadhidha D. Cinta; Hasina Raisa; Astri A. Hapsara (YASIN, 2026)
Self-control ability is an important aspect of child development because it plays a role in regulating emotions, behavior, and decision-making. Based on observations and interviews at the Muhammadiyah PCM Kembangan Children’s Orphanage, children still experienced difficulties in controlling their behavior, understanding the consequences of their actions, and making appropriate decisions. Children’s discipline also tended to depend on external supervision, so an intervention program is needed to improve self-control ability independently. This study aims to improve children’s self-control ability through a series of intervention activities designed based on James R. Averill’s self-control theory, which includes the aspects of behavioral control, cognitive control, and decisional control. This study used a quantitative approach with a one-group pretest-posttest design. The research subjects consisted of 12 children aged 8–13 years who were under the care of the Muhammadiyah PCM Kembangan Children’s Orphanage. Data were collected through observation, interviews, and a self-control questionnaire adapted from Nurfaujiyanti (2010). The intervention was implemented through five programs, namely “Misi Penjaga Ketenangan,” “Teater Cermin Ajaib,” “Buku Petualangan,” “Estafet Kuas Ajaib,” and “Misi Detektif Seribu Wajah.” The results showed a significant improvement in children’s self-control ability after participating in the intervention, with the mean total score increasing from 41.67 in the pre-test to 49.25 in the post-test. The statistical test results showed a significance value for the total score of 0.000 (p < 0.05), indicating that the intervention was effective in improving behavioral control, cognitive control, and decisional control among children in the orphanage. The conclusion of the study affirms that structured activity-based psychological intervention can be a relevant approach to strengthening children’s self-control ability. The implications of this study provide practical contributions for caregivers, educators, and social institutions in designing guidance programs that support children’s independence, discipline, and decision-making in a more adaptive manner.